Health Literacy dan Perilaku Pencegahan terhadap TBC Paru Anak di Puskesmas Bandarharjo - Fitria Anggraini; Aprianti .; Dian Puspitaningtyas Laksana; Fitria Wulandari (Jurnal Kesehatan, 2021)
Pediatric pulmonary tuberculosis cases in Semarang City in 2017 increased compared to2016 with 916 cases. Puskesmas Bandarharjo is the area with the highest TB sufferers inSemarang City. The discovery of pediatric TB cases at Puskemas Bandarharjo in 2016-2019fluctuated up to 43 cases spread across 4 urban villages,. The high number of tuberculosiscases in Semarang City can be caused by low health literacy. Low health literacy will affectpulmonary tuberculosis prevention behavior so that it will increase the number of cases ofpulmonary tuberculosis. The purpose of this study is to determine the relationship betweenhealth literacy and parental prevention behavior against cases of pediatric pulmonarytuberculosis at Puskesmas Bandarharjo, Semarang. Primary data collection was carried outby Puskesmas Bandarharjo cadres using a questionnaire The questionnaire containsquestions that related the demographic characteristics, 10 questions about tuberculosisprevention behavior and 15 questions regarding health literacy. The sampling techniquewas consecutive sampling with a total sample of 92 people. The analysis used in this researchis univariate and bivariate analysis. Univariate analysis was carried out to provide anoverview of the research variables in the form of a percentage distribution. Bivariateanalysis was performed using chi-square to determine the relationship of each variable.There is a significant relationship between parental income per month with the incidence ofchild pulmonary tuberculosis p value 0,037 (p<0,005) and there is no significantrelationship between the age of the respondent p value 0,788 (p>0,050), the level of parentaleducation p value 0,842 and 0,407 (p>0,050), health literacy p value 0,059 (p>0,005) andparental prevention behavior p value 0,296 (p>0,005) towards the incidence of pediatricpulmonary tuberculosis in Puskesmas Bandarharjo Semarang. Parental income related withthe economic status of the family which contributes to the incidence of child pulmonarytuberculosis, because the parental income will lead to dwellings in densely populated, slumsettlements and it is difficult to meet children's nutritional needs. The factor that influencesthe cases of pediatric pulmonary tuberculosis is parental income.